Integrasi Etika dalam Kurikulum Akhlak: Analisis Pengajaran Gibah di Sekolah Menengah Pertama Kelas VII Pendidikan Agama Islam: The Integration of Ethics in Morals Curriculum: An Analysis of Teaching About Backbiting (Ghibah) in Grade VII Islamic Religious Education at Junior High Schools - Didin, Didin Sahidin; Asep Nursobah (Epistemic: Jurnal Ilmiah Pendidikan, 2024)
This study examines the moral curriculum within Islamic Education (PAI) for seventh-grade students in junior high school, focusing specifically on the topic of gossip (gibah). Despite its significant impact on social behavior and individual ethics, this topic is often underemphasized in educational settings. The research aims to explore how gossip is taught and its implications within the moral curriculum. Employing a qualitative research methodology, the study utilizes literature analysis, observations, and interviews to gain insights into the challenges associated with teaching this subject. The findings reveal that gossip can lead to social conflicts, strain relationships, and contribute to an unhealthy school environment. Additionally, the study highlights the potential for unethical behavior to emerge from the way gossip is addressed in educational contexts. The research underscores the need for a more holistic and integrative approach to the moral curriculum, emphasizing communication ethics, empathy, and the awareness of the consequences of one's words and actions. The study's implications suggest that a positive and progressive revision of the moral curriculum could mitigate the negative effects of gossip, fostering the development of more ethical and compassionate individuals.